Reminiscências: vozes e imagens de Cascavel-PR - Prado, Silvia Maria Soares do (2020)
This dissertation aims to study theoretical references, as well as conducting data collection with video interviews, and the production of a documentary, using testimonies from pioneers in the preservation of immeasurable values expressed in the historical, social and cultural memory of Cascavel city, from Paraná State, Brazil. Therefore, valuing the narrated stories experienced by me, connecting them with the stories of the pioneers. In short, the goal is expanding the understanding, the methodology used in the compared studies, conceptualizing the orality, the memory and the testimony as a research source. With the premise and the basis of the following theoretical, Ecléa Bosi (1995; 2003), Maurice Halbwachs (2018) and João Carlos Tedesco (2001), we prioritized the individual and collective memory, expressed by narratives that are instruments for understanding of historical value, the somewhat anonymous individuals of official history. Therefore, it is observed the expressions and impressions in which translate into information, curiosities, values and cultural knowledge. Thus, the testimonies of the pioneers bring vivid memories, in a way that express the identity and everyday stories of the city. Corroborating with their stories full of feelings, experiences and social and cultural teachings, often far from books. Finally, we mentioned the testimony of Santiago de João Moreira Salles (2007), which awakens the importance of the orality recording to preserve the stories with Salles Family. Corroborating to the production of the documentary film “Reminiscences: Voices and Images of Cascavel-PR” (2020), which brings roots and legacies from the past of the pioneers, historical photographs from the collection of the Museum of Image and Sound of Cascavel-PR and stories from the adolescence of this researcher.